2015
DOI: 10.1021/acs.jmedchem.5b01220
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Manassantin Analogues for Hypoxia-Inducible Factor 1α Inhibition

Abstract: To cope with hypoxia, tumor cells have developed a number of adaptive mechanisms mediated by hypoxia-inducible factor 1 (HIF-1) to promote angiogenesis and cell survival. Due to significant roles of HIF-1 in the initiation, progression, metastasis, and resistance to treatment of most solid tumors, a considerable amount of effort has been made to identify HIF-1 inhibitors for treatment of cancer. Isolated from Saururus cernuus, manassantins A (1) and B (2) are potent inhibitors of HIF-1 activity. To define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…The ketone and hydroxy analogs of 43 without methoxy substituents at the distal phenyl ring also retained sub‐micromolar IC 50 values (IC 50 = 0.69 μM and 0.59 μM for 48h and 48i , respectively). Analog 47 regulated HIF‐1α but not HIF‐1β, and reduced Cdk6, VEGF, and mRNA levels markedly . Mechanistically, the hit protein of manassantin A related to HIF‐1 activity is filamin A, but more work is needed to understand the exact mechanism …”
Section: Manassantin a And Analogsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ketone and hydroxy analogs of 43 without methoxy substituents at the distal phenyl ring also retained sub‐micromolar IC 50 values (IC 50 = 0.69 μM and 0.59 μM for 48h and 48i , respectively). Analog 47 regulated HIF‐1α but not HIF‐1β, and reduced Cdk6, VEGF, and mRNA levels markedly . Mechanistically, the hit protein of manassantin A related to HIF‐1 activity is filamin A, but more work is needed to understand the exact mechanism …”
Section: Manassantin a And Analogsmentioning
confidence: 99%
“…18 The similar benzimidazole analog (4) of LW6 identified through an HRE-dependent cell-based assay was supposed to regulate HIF-1 through the Hsp90-Akt pathway. The benzimidazole analog (4) reduced tumor growth by 58.6% in a mouse model and exhibited an IC 50 (human colorectal carcinoma cells). 19 LW6 was further modified in search of a better analog by replacing ring B with nicotinic and isonicotinic acid, esters, or amides.…”
Section: Adamantyl-based Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In cell-based assays manassantin A has been shown to possess therapeutic potential for the treatment of diseases involving melanin production, 5,6 atherosclerosis, 79 and cancer. 1,1012 Manassantin A exhibits cytotoxicity against a wide range of cancer cell lines including HT-29, HepG2, PC-3, and MDA-MB-231, but weak cytotoxicity against non-cancer cell lines. 1,10,11 This cytotoxic specificity makes manassantin A an attractive anti-cancer drug candidate.…”
Section: Introductionmentioning
confidence: 99%
“…19 Several manassantin A derivatives also inhibit HIF-1α in cell-based assays, some with lower IC 50 values than the parent compound. 12,1618 One prominent HIF-1α target angiogenic gene, vascular endothelial growth factor (VEGF), is also inhibited by manassantin A. 12,17,18 While many cell-based studies have shown inhibition of HIF-1α by manassantin A, the molecular mechanism(s) by which this inhibition occurs are unknown.…”
Section: Introductionmentioning
confidence: 99%